PELATIHAN KADER KESEHATAN JIWA DESA UNDAAN LOR DENGAN CARA DETEKSI DINI DENGAN METODE KLASIFIKASI - Anny Rosiana M; Rizka Himawan; Sukesih - (Universitas Muhammadiyah Semarang, 2015)
Background: Health not only be physically but also in terms of the mental. Integrated service post (Posyandu) is an effort to empower the community to optimize promotive, preventive, curative and rehabilitative services for the growth and development of mental health. Early detection with classification technique obtained more accurate data because the classification of a healthy family, relatives and family disruption risk. This classification is done by cadres after getting the training cadre of mental health. Destination: the lack of data makes it easier cadre early detection and health professionals to conduct further observation and treatment. Mental health workers is also increasing its ability in terms of promotion, prevention and treatment of mental patients was at home and in making referrals in cooperation with the local village, along with officers from the health center Undaan Lor. Methods: Descriptive by describing the course of the process of community service. With the recruitment of cadres, cadres training of mental health, early detection.Results: mental health worker rekriutmen as many as 25 people at the formation of the organizational structure of mental health cadres in syahkan by Undaan Lor village government, after it held a training cadre of mental health in cooperation with the Government of Undaan Lor village, health center Ngemplak and IBM Team on date 16 to 18 June 2015. After following Cadre Training Mental Health, ladies and cadres are increased knowledge and the data generated in the population health RW 3 and RW4 with classification methods such as healthy families, family risk, the family with the disorder.Keywords: Kader, early detection, classification method.